Adsorpsi Pb (II) Oleh Arang Aktif dari Tumbuhan Mangrove Avicennia marina - Rina Andayani; Yuli Ainun Najih (Jurnal Riset Kelautan Tropis (Journal Of Tropical Marine Research) (J-Tropimar), 2020)
Heavy metals are substances that are harmful to human health. Heavy metals are usually found in the form of dissolved ions. One type of heavy metal is lead (Pb (II)). One way to reduce the Pb (II) content is by using the adsorption process using activated charcoal. Several materials from nature have been studied as materials of active charcoal for adsorption of heavy metal Pb (II), including oil palm shells, cassava peels, siwalan coir, and bamboo. Avicennia marina magrove plant is a species that is quite widely available in Surabaya. This study aimed to analyze the adsorption process of activated charcoal from mangrove Avicennia marina against heavy metal Pb (II). The method used includes three stages, namely (1) carbonization; (2) charcoal activation; (3) adsorption of Pb (II). From the research that has been done, it could be concluded that the activation process of charcoal into activated charcoal using ZnCl2 activator can open the pores on the surface of the charcoal, so that activated charcoal can adsorb Pb. The greater the initial concentration, the lower the adsorption% with the same amount of adsorbent. The process of Pb (II) isothermal adsorption by activated charcoal from the mangrove Avicennia marina, more closely follows the Langmuir isothermal adsorption model which had a value of R2 = 0.9968, while for the Freudlinch isotherm adsorption model had a value of R2 = 0.9474.